Information systems and patients’ empowerment around patients’ pathways: the French and the Portuguese scenarios - Bourret, Christian; Pestana, Olivia (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
In this work, the authors undertake a descriptive comparison of the French and Portuguese national information systems, especially related to recent developments towards patients’ management of their own data.  It is clear that patients’ participation in their health management is growing worldwide and that it is crucial for their wellbeing. On the other hand, the citizens’ circulation in a professional or leisure context, may boost their use of international health information systems, as long as they are compatible with interoperability standards.  Nevertheless, some ethical considerations have to be explored, as well as information security issues. They constitute important challenges to tackle in the future with cooperation at a regional, national and European level.